تأثير استخدام نموذج التدريس خمن الكلمة على استيعاب الطالبات للمفردات في المرحلة المتوسطة - Putri, Cahyananda Dwi; Karo, Tiy Kusma Robi; Anhar, Khairul (ANWARUL, 2024)
The purpose of this research is to determine the effect of using the "Guess the Word" teaching model on vocabulary comprehension among middle school female students at Abdullah bin Masoud Institute in Asahan, North Sumatra. The methodology used in this research is field quantitative research of an experimental type, utilizing statistical methods. The results of this research show that the average vocabulary score of students using the "Guess the Word" teaching model is 82.32, while the average vocabulary score of students without using the model is 62.14. The t-test result of to 3.025 is greater than the critical value of tt at a 5% significance level, which is 2.018. Therefore, the null hypothesis is rejected, and the alternative hypothesis is accepted. In conclusion, the use of the "Guess the Word" teaching model has a positive effect on vocabulary comprehension among middle school female students at Abdullah bin Masoud Institute in Asahan, North Sumatra.